(untitled) (BIRDEM Medical Journal, 2012)
Gastric teratomas are extremely rare tumors. A six year old boy presented with abdominal mass. Ultrasound of abdomen showed mixed echogenic lesion. CT scan showed a mass with solid and cystic components and internal calcifications. At operation a tumor arising from the posterior wall of the stomach was found. It was exogastric as well as endogastric in location. Histopathological examination revealed a mature teratoma. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12329 (Birdem Med J 2012; 2(2): 121-123)